EVOLUTION OF CONCEPT OF «HUMAN RESOURCE MANAGEMENT» - M. Dyakonova; F. Sharipov (Вестник университета)
The evolution of such concept as human resources, and its definitions given by domestic and foreign scientists are considered. The relevance of the theory of human resource management and possibilities of its application in practical management of an organization is proved. Main problems of human resource management are defined. A priority objective for practitioners in the field of human resource management at the current stage of economic development is the introduction of new forms and methods of work organization which will contribute to the maximum disclosure of potential human capabilities. This is a topical subject for the coaches who train specialists in the field of international business.